Zur Semantik der Tages- und Epochenbezeichnungen im Deutschen und Polnischen - Jankowska, Iwona (Studia Germanica Posnaniensia, 2018)
The article refers to Ph.D. dissertation in which the author investigated adverbials of time in German and Polish. Using a similar method of analysis, namely establishing the relations occurring between the point of time of the event, the reference and the speech act, the author describes the usage of definitions of a day and longer periods (epochs). The author refers at the same time to simple formulas of formal logic and juxtaposes all the relevant expressions in both languages.